2009
DOI: 10.1080/08263663.2009.10816977
|View full text |Cite
|
Sign up to set email alerts
|

La Gouvernance Rurale au Mexique en Réponse À La Vulnérabilité Paysanne Extrême

Abstract: Resume. Depuis 1' ouverture des marches et la dereglementation commerciale a l'echelle mondiale, de nouvelles opportunites de mise en marche ont emerge pour les producteurs agricoles mexicains, notamment dans les secteurs de !'horticulture et du maYs, ce demier faisant l'objet d'une demande croissante de la part des usines americaines de production d'ethanol. Parmi les strategies deployees par l'Etat mexicain pour s'inserer dans l'economie mondiale, on retrouve les politiques agricoles qui encouragent 1' expor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…In other words, with sufficient capacity to integrate into the market. See Gravel (2009 In effect, despite what had been written, it has been shown that guetza is the collective work that was institutionalized during the colonial era. Tequio is a náhuatl word that designates the community service of the adult members of the community, whose origin dates back to colonial times.…”
Section: Notably Studies Of Wp5 "Building and Exchanging Knowledges mentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, with sufficient capacity to integrate into the market. See Gravel (2009 In effect, despite what had been written, it has been shown that guetza is the collective work that was institutionalized during the colonial era. Tequio is a náhuatl word that designates the community service of the adult members of the community, whose origin dates back to colonial times.…”
Section: Notably Studies Of Wp5 "Building and Exchanging Knowledges mentioning
confidence: 99%
“…By the 1990s the ejidos had been privatized and extension Nevertheless, political discourse has continued to defend the importance of developing autonomous and efficient agrifood systems. In a country where only 6% of farmers are classified as "modern", 12 the Mexican Government has had to propose various programmes and measures to mitigate the impacts of rising food prices for the poorest strata of the population (Gravel, 2009). The main measures aimed at the poorest farmers were a distribution of grants according to cultivated acreage (such as the so-called Procampo Programme) and aid to the poorest women (Progresa/Oportunidad).…”
mentioning
confidence: 99%
“…Governança não é sinônimo de governabilidade. Aqui entende-se a governabilidade, vinculada ao sistema político-institucional, como a dimensão estatal do exercício do poder que direciona o desenvolvimento do controle e da ordem, bem como possui atributos considerados essenciais para o exercício do governo (GRAVEL e LAVOIE, 2009).…”
Section: Introductionunclassified
“…Com isto, envolve os diversos atores não estatais no processo de negociação e tomada de decisão. Em um plano mais amplo, a governança engloba a sociedade como um todo (ROSENAU, 2002;GONÇALVES, 2006;GRAVEL e LAVOIE, 2009).…”
Section: Introductionunclassified
“…In a country where only 6% of farmers are classified as "modern", 12 the Mexican Government has had to propose various programmes and measures to mitigate the impacts of rising food prices for the poorest strata of the population (Gravel, 2009). The main measures aimed at the poorest farmers were a distribution of grants according to cultivated acreage (such as the so-called Procampo Programme) and aid to the poorest women (Progresa/Oportunidad).…”
mentioning
confidence: 99%